ANTECEDENTS OF PRIVACY PROTECTION BEHAVIORS AT THE VERTICAL AND HORIZONTAL LEVELS - Bartol, Jošt; Vehovar, Vasja; Petrovčič, Andraž (AoIR Selected Papers of Internet Research, 2023)
Internet users face privacy threats when using online services. Privacy protection behaviors, such as adjusting privacy settings, can alleviate some of these threats. Research shows that individuals’ privacy protection behaviors (PPBs) depend on their socio-demographics characteristics, digital engagement, privacy concerns, and online privacy literacy (OPL). In addition, it has been suggested that due to the complexity of privacy issues online, an adequate level of OPL is required to translate privacy concerns into protective actions. Although previous research examined the antecedents of PPBs at a general level, it has rarely made a clear distinction and comparison between PPBs aimed toward the practices of institutions (vertical level) and those aimed toward other internet users (horizontal level). This is somewhat surprising given that many scholars underscored the importance of context in online privacy-related matters. Therefore, this study compared the antecedents of PPBs at the general, vertical, and horizontal levels. To this end, we tested three models to examine how socio-demographic characteristics, digital engagement, privacy concerns, and OPL influence PPBs at the general, vertical, and horizontal levels, and assessed whether OPL moderates the relationship between privacy concerns and PPBs at different levels. The models were tested using linear regression on a nation-wide sample of 1,015 internet users aged 18+ from Slovenia. The analysis revealed important differences between the levels in case of gender, age, and privacy concerns, but not OPL.